Functional role of the biofilm regulator CsgD in Salmonella enterica sv. Typhi - Juan F. González; Juan F. González; Baileigh Laipply; Baileigh Laipply; Victoria A. Sadowski; Victoria A. Sadowski; Matthew Price; Matthew Price; John S. Gunn; John S. Gunn; John S. Gunn (Frontiers in Cellular and Infection Microbiology)
IntroductionTyphoid fever is an infectious disease primarily caused by Salmonella enterica sv. Typhi (S. Typhi), a bacterium that causes as many as 20 million infections and 600,000 deaths annually. Asymptomatic chronic carriers of S. Typhi play a major role in the transmission of typhoid fever, as they intermittently shed the bacteria and can unknowingly infect humans in close proximity. An estimated 90% of chronic carriers have gallstones; biofilm formation on gallstones is a primary factor in the establishment and maintenance of gallbladder carriage. CsgD is a central biofilm regulator in Salmonella, but the S. Typhi csgD gene has a mutation that introduces an early stop codon, resulting in a protein truncated by 8 amino acids at the C-terminus. In this study, we investigate the role of role of CsgD in S. Typhi. MethodsWe introduced a fully functional copy of the csgD gene from S. Typhimurium into S. Typhi under both a native and a constitutive promoter and tested for red, dry, and rough (Rdar) colony morphology, curli fimbriae, cellulose, and biofilm formation. Results and discussionWe demonstrate that although CsgD-regulated curli and cellulose production were partially restored, the introduction of the S. Typhimurium csgD did not induce the Rdar colony morphology. Interestingly, we show that CsgD does not have a significant role in S. Typhi biofilm formation, as biofilm-forming capacities depend more on the isolate than the CsgD regulator. This data suggests the presence of an alternative biofilm regulatory process in this human-restricted pathogen.